RELIGIOUS FOUNDATION IN GUIDANCE AND COUNSELING - Siregar , Alfin (The Islamic Education and Multiculturalism Foundation, 2019)
This paper aims to illustrate the important value of religion in humanlife in the Modern era. However, internalization of religious understanding canonly be disseminated through education (counseling guidance). Furthermore,many Indonesians embrace eastern culture, so that the implementation ofcounseling guidance at the educational level should have considered theReligion side in the face of changing times. This paper uses a library researchapproach, where data is obtained and collected from literature studies. Analysisof the data in this paper requires the author's important role in interpreting thedata. The findings resulted that religion became a basic milestone in educationalservices (counseling guidance). Science and Religion must be balanced, so thatreligion can be a guide for someone to act, so does Science become a drivingforce in sustaining the progress of the times.